EFISIENSI SISTEM TATANIAGA ROTAN DI KALIMANTAN TIMUR - Satria Astana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
The efficiencv of rattan marketing system in East Kalimantan. Two criteria were develoaed and used to analyse The first criterium is that the marketing system is assumed to be efficient when its marketing margin is less than 50% of the consumer price. Secondly. eventhough the marketing margin is under 50%, the marketing system is assumed to be ineffcient when the profit margin of the system tends to accumulate in one trader or more. The results of the study reveal that the rattan marketing system in East Kalimantan is in -efficient. As it is shown, based on the price spread analyses. by the marketing margin of the system that is 66.67%. This high margin is due to the water content. cost which accounts for 81.25% and 62.52% of the marketing cost .for intermediate and inter islanders tarders, respectively. Meanwhile. the profit margin of the system tends to accumulate in one trader, that is the inter island trader. In fact, the inter. islands trader gains the profit of 12,01%. Markering cost ii only 21.32% of the consumer price. On the other hand, the intermediate trader who spends the marketing cost as much as 24. 62% of the consumer price gains the profit of 8. 72% only.The accumulation of profit margin on the inter islands trader would imply. that in the case of the market price in-creases or the marketing cost decreases, profit margin could not be distributed among other operators within marketing channels. including the rattan farmers. As a result. farmers may decrease their production. This may further Comaound the reduction of domestic rattan trade caused. by the rattan export banpplicies. Therefore,, without better distribution of profit .margin among operators within marketing system, the shortage of rattan supply in the domestic market may not be avoided.